Bone health among patients with primary aldosteronism : a systematic review and meta-analysis - Loh, Huai Heng; Yee, Anne; Loh, Huai S. (EDIZIONI MINERVA MEDICA, 2019)
INTRODUCTION: Recent studies showed a possible association between hyperaldosteronism and secondary hyperparathyroidism leading to reduced bone health, however results are conflicting. EVIDENCE ACQUISITION: We conducted a meta-analysis to evaluate the relationship between primary aldosteronism (PA) with bone biochemical markers and to assess bone mineral density in patients with primary aldosteronism. EVIDENCE SYNTHESIS: A total of 939 subjects were examined (37.5% with PA). Patients with PA had signifi- cantly higher serum parathyroid hormone, lower serum calcium, higher urine calcium excretion and higher serum alkaline phosphatase compared to patients without PA, with no significant difference in serum vitamin D between both groups. Bone mineral density of lumbar spine, femoral neck and total neck of femur were similar between two groups. With PA treatment, there was a significant increment in serum calcium and reduction in serum parathyroid hormone. CONCLUSIONS: PA is associated with hypercalciuria with subsequent secondary hyperparathyroidism. This potentially affects bone health. We recommend this to be part of complication screening among patients with PA. (Cite this article as: Loh HH, Yee A, Loh HS. Bone health among patients with primary aldosteronism: a systematic review and meta-analysis. Minerva Endocrinol 2019;44:000–000. DOI: 10.23736/S0391-1977.18.02867-5)